Pengintegrasian pemikiran komputasional melalui aplikasi mudah alih untuk meningkatkan disposisi pemikiran komputasional - Isra Khasyyatillah; Kamisah Osman; Hazrati Husnin (Penerbit Universiti Kebangsaan Malaysia, 2024)
In modern education, there is a significant increase in the use of digital innovations to enhance students’ Computational Thinking (CT) disposition. However, the integration of CT into educational curricula often faces various challenges. This study examines the eff ects of integrating CT through a mobile application on students’ CT disposition. Using a quasi-experimental design, the research involved 60 students divided into two groups: the treatment group using a CTfocused mobile application, and the control group following traditional teaching methods. Both groups underwent pretests and post-tests to assess changes in CT disposition. Statistical analysis, including repeated measures MANOVA, indicated a significant improvement in CT disposition among those using the mobile application. The study highlights the eff ectiveness of using mobile applications in integrating CT to enhance students’ CT skills. Additionally, it underscores the importance of CT elements in education to promote more inclusive teaching practices. Overall, the findings confirm the value of mobile learning applications in advancing CT in education.